Ranking of Factors Causing Construction Project Changes in UAE Mega Construction Projects - AlAmeri, Abdulla; Abdul Rahman, Ismail; Ngah Nasaruddin, Nur Ain (International Journal of Sustainable Construction Engineering and Technology, 2020)
Many construction projects are facing changes along its life cycle due to different reasons. Once the project faces change, it has a negative impact on the concerned parties. This paper presents a study on identifying main reasons/causes to construction changes in UAE Mega projects. Literature review conducted identified 58 causes of changes which were categorized in three groups which are namely client, consultant and contractor groups. These lists of causes were used to develop questionnaire to uncover the significant causes to the changes from the UAE construction practitioners’ perspective. A questionnaire survey was conducted and 218 valid responses were considered for the analysis using mean score index. It was found that lack of coordination is the most significant cause in client group, then poor site management team for consultant group and finally, poor inspection & supervision by contractor in contractor group. It is hope that the result of this study can minimize the potential changes during implementation of the project’s construction.